2004
DOI: 10.1177/0148607104028005348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a nutritional supplement on the immune response and cytokine production in free‐living Chilean elderly

Abstract: This nutritional supplement increased innate immunity and protection against infections in elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 28 publications
1
82
1
2
Order By: Relevance
“…No effect on antibody response to vaccines Significantly lower incidence of infection after 12 months, in particular respiratory illnesses, in treatment group v. controls (P = 0·034) (76) H1N1 following intervention with Lactobacillus fermentum VRI 003 for 6 weeks in total (vaccination after 2 weeks), but there were no differences for other subunits. The average number of days of respiratory symptoms was reduced from 5 to 2 d (73) .…”
Section: Probiotics and The Immune Response To Influenza Vaccinationmentioning
confidence: 95%
See 1 more Smart Citation
“…No effect on antibody response to vaccines Significantly lower incidence of infection after 12 months, in particular respiratory illnesses, in treatment group v. controls (P = 0·034) (76) H1N1 following intervention with Lactobacillus fermentum VRI 003 for 6 weeks in total (vaccination after 2 weeks), but there were no differences for other subunits. The average number of days of respiratory symptoms was reduced from 5 to 2 d (73) .…”
Section: Probiotics and The Immune Response To Influenza Vaccinationmentioning
confidence: 95%
“…Four out of eight of the studies investigating the impact of probiotics on responses to influenza vaccination were conducted in healthy adults (72)(73)(74)(75) , while the remaining four were conducted in elderly subjects (76)(77)(78)(79) ; three of these were conducted in institutionalised individuals (77)(78)(79) (Table 1). The largest of the trials conducted in elderly subjects (n 362 and 375 on probiotic and placebo, respectively) demonstrated no effect of L. casei Shirota on respiratory infections, seroprotection, seroconversion or mean antibody titres (79) .…”
Section: Probiotics and The Immune Response To Influenza Vaccinationmentioning
confidence: 99%
“…Also amino acids, the modules of proteins, contribute to the maintenance of an intact immune system by ensuring the generation of the scavenger glutathione, for example. A high impact on beneficial intestinal bacteria, which boost immune properties, could be demonstrated by synbiotica (probiotica and prebiotica) [77].…”
Section: Elderly Peoplementioning
confidence: 99%
“…It has been proposed that enhancement of probiotic bacteria in the intestines provides advantages to the host [19]. It was also demonstrated that synbiotic nutritional supplements consisting of probiotic L. paracasei and prebiotic fructooligosaccharides efficiently increased NK cell activity in elderly people [20]. Recently, we have shown that L. casei ssp.…”
Section: Introductionmentioning
confidence: 99%